Singlet oxygen production by a crude oil from the San Jorge Gulf Basin, Argentina - López, Rosmari Marisa (2018)
The quantum yields for singlet oxygen production by diluted solutions of an Argentine crude oil and its SARA (saturates, aromatics, resins and asphaltenes) fractions were obtained by direct detection of the characteristic phosphorescence following monochromatic excitation at 355 nm. The most efficient sensitizers of singlet oxygen in organic media are crude oil, maltenes and aromatics fractions (values of singlet oxygen quantum yield are around 0.7), and resins (values around 0.1) are the poorest. Also, the quenching of singlet oxygen by the crude oil and its fractions was investigated; the asphaltenes and the petroleum are relatively efficient quenchers of singlet oxygen.